Identifikasi Perubahan Pemukiman Suku Bajo Di Desa Lemito, Kabupaten Pohuwato, Provinsi Gorontalo - Febrianti, Febrianti; Yusuf, Daud; Kobi, Wiwin (-, 2025)
Identification of Changes in Bajo Tribe Settlements in Lemito Village, Pohuwato Regency, Gorontalo Province. This study aims to identify changes in the settlements of the Bajo tribe in Lemito Village, Pohuwato Regency, as well as to identify the social, economic, and environmental factors that influence these transformations. The research methods used include spatial analysis of satellite imagery from 2011 to 2025 combined with surveys and field interviews. The results show that the settlement area has increased significantly from 1.85 hectares in 2011 to 3.65 hectares in 2025. Population growth, which reached 1,099 people, also triggered an increase in residential density and the conversion of mangrove land into built-up areas. Socioeconomically, 75% of the community has switched their livelihoods to the land sector, while 62.5% of respondents assessed that the Bajo tribe's culture has begun to experience a decline in traditional values. These findings indicate that the changes in the Bajo tribe's settlements are a form of community adaptation to the tide of modernization and coastal development